Implementation of the Moving Particle Semi-implicit method to predict the drag resistance coefficient on 2D (2016)
A dam break problem and the flow around a 2D submerged body on different scenarios were solved with the original Moving Particle Semi-implicit (MPS) method proposed by Koshizuka and Oka in 1996 -- The results of this study showed that although the original method reproduces the free surface of the fluid on the dam break computation, it can not accurately compute the pressure distribution over the submerged bodies -- It was found that the free surface was inaccurate when negative pressures were present in the particle domain -- Also, when modelling the interaction of a solid immersed in a fluid, the simulation exhibited stability issues and solid penetration -- Several modifications of the original MPS were studied, implemented and tested -- This thesis proposes a modified Moving Particle Semi-implicit (MPS)method for modelling immerse bodies in an free surface flow -- The MPS method is based on the prediction-correction calculation of the velocity field based on the Helmhotz-Hodge decomposition -- Initially the predicted velocity is calculated based on the viscous and external forces terms and then corrected by the gradient of the pressure which is obtained by the solution of the Poisson Pressure’s equation – This thesis shows how small variations in the source term of the Poisson Pressure’s equation can destabilise or stabilise simulations -- One of the main result of this research is an improved stability by means of a reformulation of the Poisson Pressure equation and the aid of relaxation factors -- Also, the pressure gradient was computed for non free surface particles only -- The results show that, although pressure fluctuations were still present, good results were obtained when compared the drag coefficient to the reported values in the literature